Glucagon‐like peptide‐1 receptor agonists improve biomarkers of inflammation and oxidative stress: A systematic review and meta‐analysis of randomised controlled trials. Issue 8 (6th May 2021) - Bray, Jonathan J. H.; Foster‐Davies, Harri; Salem, Ahmed; Hoole, Amy L.; Obaid, Daniel R.; Halcox, Julian P. J.; Stephens, Jeffrey W.
Abstract: Aim: To conduct a meta‐analysis and systematic review to examine the effects of glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) on clinical biomarkers of inflammation and oxidative stress in patients with type 2 diabetes. Methods: Medline, Embase and the Cochrane Library were searched for randomised controlled trials (RCTs) that examined changes with GLP‐1RAs in a priori selected biomarkers of inflammation: C‐reactive protein (CRP), adiponectin, tumour necrosis factor‐alpha (TNFα), plasminogen activator inhibitor‐1, interleukin‐6, leptin; and of oxidative stress: malondialdehyde (MDA); 8‐iso‐prostaglandin F2α; and 8‐hydroxy‐2′‐deoxyguanosine (8‐OHdG). Results: We included 40 eligible RCTs (n = 6749) with a median follow‐up of 6 months, a mean participant age of 53.1 years, 56.3% females, glycated haemoglobin (HbA1c) 55.6 mmol/mol, body mass index 28.8 kg/m 2 and diabetes duration 7.46 years. Analysis of GLP‐1RAs versus standard diabetes therapies or placebo revealed significant reductions in CRP, TNFα and MDA, and significant increases in adiponectin for (mean difference −0.54 mg/L [−0.75, −0.34]; standard mean difference [SMD] −0.39 [−0.62, −0.15]; SMD −0.84 [−1.61, −0.06] and SMD 0.30 [0.12, 0.49], respectively [95% confidence intervals]). Systolic blood pressure decreased significantly and was significantly and strongly correlated with a reduction in CRP. Homeostatic model assessment of insulin resistance was also significantly correlated with a reduction in CRP, but HbA1c was not. Conclusions: There is strong evidence supporting clinically relevant anti‐inflammatory and antioxidant effects of GLP‐1RAs. This may be used to guide future targeted clinical use of GLP‐1RAs and the development of medications seeking to target the cardioprotective properties of GLP‐1RAs.